Simultaneous Minimally Invasive Coronary Artery Bypass Grafting and Lung Resection - Lianyong, Jiang; Pengkai, Gao; Xuefeng, Zhang; Fangbao, Ding; Hao, Liu (The Thoracic and Cardiovascular Surgeon, 2023)
Background The best surgical treatment strategy for coexisting coronary artery disease (CAD) and lung cancer (LC) remains controversial. This study analyzed the safety and efficacy of a simultaneous minimally invasive procedure for patients with CAD and LC.Methods Patients who underwent simultaneous minimally invasive off-pump coronary artery bypass grafting and lung resection from January 2016 to December 2021 were retrospectively analyzed. The procedure was performed in the fourth intercostal space through a small left anterolateral minithoracotomy. Harvesting of the left internal mammary artery (LIMA) and sewing of the anastomoses were performed under direct vision. Lung resections were performed with or without the assistance of a thoracoscope.Results Sixteen patients were included with a mean age of 67.13 ± 10.61 years. Procedural success occurred in all patients with a mean operative time of 366.88 ± 94.48 minutes. All patients received at least one coronary artery bypass LIMA graft. Pneumonectomy, lobectomy, segment resection, and wedge resection were performed in one (6.25%), eight (50%), two (12.5%), and five (31.25%) patients, respectively. There were no perioperative deaths or new myocardial infarctions. Complications included one case of postoperative bleeding, two lung infections, two cases of atelectasis, one case of pleural effusion, and one case of cardiac arrhythmia. All the patients were followed up for 1 to 57 months, cancer recurrence occurred in two patients, and one patient died. The remaining patients showed no evidence of tumor recurrence or myocardial infarction.Conclusion This simultaneous minimally invasive procedure is safe and effective for selected patients with CAD and LC.
Keywords: coronary artery bypass grafting; lung cancer; treatment; minimally invasive; surgery; complications; thoracoscopy